Gitanjali (Song Offerings): a Bibliometric Study - Ray, Partha Pratim; Sen, B. K. (Journal of Information and Knowledge, 2012)
Rabindranath Tagore (1861-1941) received Nobel Prize for Gitanjali (Songs Offerings) in 1913 which is a collection of poems from different kavyagrantha (book of poems). The present paper is an attempt to study the growth of poems of Gitanjali, their lengths, places and dates of writings, use of words, rank frequency of different words and to find out whether Gitanjali follows any bibliometric law. The study also tries to find justification of the title Gitanjali with the help of bibliometric techniques. It is observed from the study that many poems of Gitanjali are songs, written long before the publication and submission of Gitanjali for Nobel Prize .The rank-frequency distribution of words in Gitanjali do not follow Zipf‟s law but justiies the title of the kavyagrantha.